METAFORA KONSEPTUAL PERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DALAM SURAT KABAR DARING KOMPAS - Faradhiba Salsabila; Tajudin Nur; Sutiono Mahdi; Agus Suherman Suryadimulya (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
Conceptual metaphors are used by humans to communicate, including the mass media. Concepts are mapped by humans to understand the essence of meaning networks (Arimi, 2015). Research on the conceptual metaphor for the term PPKM can be carried out to look at the mass media's depiction of terms which are government policies in dealing with the Covid-19 pandemic. The purpose of this study is to describe the types of conceptual metaphors and concepts of meaning for the term PPKM in the online newspaper Kompas. The theory used is Lakoff and Johnson (1980) to define conceptual metaphor. This research method is qualitative method. Data collection was carried out by observing and note-taking methods. The results of the study found there are 25 conceptual metaphors. Based the types of conceptual metaphors, 8 structural metaphors, 10 orientational metaphors, and 7 ontological metaphors. This research found there were 10 concepts of the meaning of the term PPKM, namely PPKM is restraint, PPKM is a scenario, PPKM is a room, PPKM is long, PPKM is wide, PPKM is walking, PPKM is down, PPKM is a brake, PPKM is a road, and PPKM is a tree.